THE EFFECT OF ARBUSCULAR MYCORRHIZAL FUNGI (AMF) AND ORGANIC FERTILIZERS ON MOLER DISEASE AND SHALLOT PRODUCTIVITY IN PEAT SOIL - Warman, Riki; Rianto, Fadjar; Sasli, Iwan (Departement of Agrotechnology, Agriculture Faculty, Universitas Lampung, 2025)
ABSTRACTMoler is an important disease of shallot plants caused by Fusarium oxysporumattack so that it has an impact on decreased production and even crop failure. The application of Arbuscular Mycorrhizal Fungi (AMF) and organic fertilizers is one of the efforts to control moler disease by increasing plant resistance and suppressing disease development. The aim of the study was to examine the role of AMF and organic fertilizers in increasing resistance to moler disease and to increase the growth and yield of shallot. The research was conducted at the visitor plot in BPTP West Kalimantan, and the Laboratory Plant Disease Faculty of Agriculture Tanjungpura University, from October 2020 to April 2021. The experiment was arranged using a random complete design splitplot. The main plot of mycorrhizal treatment (without mycorrhizae, aplication of mycorrhizal). Sub-plots with doses of chicken manure (without chicken manure, 3 ton ha-1.6 ton ha-1, 9 ton ha-1, 12 ton ha-1, and 15 ton ha-1). The ability of AMF in increase resistance of shallot plants by prolonging the incubation period of the disease, reducing the incidence and severity of the disease and reducing the rate of infection and the severity of moler disease. The chicken manure applied was only able to increase tuber weight per clump and plant dry weight, but was not able to suppress the development of moler disease. The growth response due to mycorrhiza of shallots decreased along with the increase in the dose of organic fertilizer applied.